2012
DOI: 10.1007/s10457-012-9500-1
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variation in fruit and seed morphology of Adansonia digitata L. (baobab) in five selected wild populations in Malawi

Abstract: Adansonia digitata L (Baobab) is widely distributed throughout Sub-Saharan Africa stretching from Senegal to Sudan, and from Ethiopia to Natal. Information of phenotypic and genetic variation is a prerequisite for the domestication and improvement of baobab fruits from the wild. A study was done to determine within and between provenance variability in fruit and seed characteristics of five populations selected from four silvicultural zones and assess whether morphometric traits could delineate populations fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 20 publications
(22 reference statements)
4
20
0
Order By: Relevance
“…The mean fruit lengths recorded in the current study (13.9–16.5 cm, Table 6) were in the range of those found by Sanchez et al (2011c) in Mali and Malawi (15.7–22.2 and 12.9–17.6 cm, respectively), as well as reported by Munthali et al (2012) from Malawi (11.9–16.5 cm). We used CV values to evaluate the impact of genetic or environmental factors on morphometric fruit traits.…”
Section: Discussionsupporting
confidence: 81%
“…The mean fruit lengths recorded in the current study (13.9–16.5 cm, Table 6) were in the range of those found by Sanchez et al (2011c) in Mali and Malawi (15.7–22.2 and 12.9–17.6 cm, respectively), as well as reported by Munthali et al (2012) from Malawi (11.9–16.5 cm). We used CV values to evaluate the impact of genetic or environmental factors on morphometric fruit traits.…”
Section: Discussionsupporting
confidence: 81%
“…Despite that Chikwawa and Mangochi (Malawi) synchronized with Mudzi, Matebeleland North, Matebeleland South, Magamba, Ngundu (Zimbabwe), Siavonga (Zambia) and Kalimbeza (Namibia) genotypes but they are from different ecological zones in terms of latitude and altitude, this therefore may signify genetic influence [12,13]. This is in agreement with reports of Munthali et al, [17] where similarities in phenotypic and genetic attributes between geographically different populations of Adansonia digitata were attributed to genetic closeness. Consequently, the overlapping in flowering between populations, provide opportunities for hybridizing selections made in the populations without the need for storing pollen and conducting control pollinations which is expensive.…”
Section: -1-variations In Time For Bud Set To Flower Opening (Anthesis)supporting
confidence: 84%
“…Tree to tree variations in fruit production are of paramount importance and commonly used by geneticists during selection for domestication and tree breeding. It offers a wider chance for a combined selection to be carried out both at provenance, family and individual tree level to attain high genetic gains [17,44]. Therefore, continued monitoring for fruit production and sex change among genotypes is required for several consecutive seasons before effecting selection of those trees that do not exhibit mast seeding.…”
Section: -5-fruit Productivity Of S Birrea In 2016/2017 and 2017/20mentioning
confidence: 99%
“…As well as, research results on Dalbergia sissoo Roxb, (Singh et al 2011), Acacia tortilis (Abdelbasit et al 2014), Pinus ponderosa (Agera and Stettle 1983), Adansonia digitata (Munthali et al 2012) and Prunus nepaulensis (Shankar and Synrem, 2012) showed that the clonal effect was dominant on the size and weight of seeds. In fact, the seed size, related to genetics other than indicated by clones, is also shown by the relation of seed size and provenance, for instance on Jatropha curcas (Guan et al 2013), Adansonia digitata L. (Munthali et al 2012). Sclerocarya birrea (Mkwezalamba et al 2015) and Faidherbia albida.…”
Section: Discussionmentioning
confidence: 89%
“…Genetic factor is also indicated by some studies which were exploring the relationship of seed size and provenance (Ager and Stettle 1983;Singh et al 2011;Munthali et al 2012;Shankar and Synrem 2012;Munthali et al 2012;Guan et al 2013;Abdelbasit et al 2014;Fredrick et al 2015;Mkwezalamba et al 2015). Some characteristics of fruit and seed are influenced by environmental factors too, such as altitude, temperature and agronomic practices (Quarda et al 2008).…”
Section: Introductionmentioning
confidence: 99%